The Nucleus Deposit: Superposed Au–Ag–Bi–Cu Mineralization Systems at Freegold Mountain, Yukon, Canada. Issue 4 (October 2016) - Bineli Betsi, Thierry; Lentz, David R.; Mcfarlane, Chris
Abstract: In this paper we present titanite U–Pb (both single crystal CA ID‐TIMS and in situ LA ICP‐MS) data, coupled with ore and gangue mineralogy and geochemical (both lithogeochemistry and microanalysis) data from the Nucleus Au–Ag–Bi–Cu deposit, in the Yukon (Canada) portion of the Tintina Au province. Arsenic‐bearing Au–Ag–Bi–Cu mineralization at Nucleus consists of two distinct styles of mineralization including: (i) reduced Au skarn and sulfide replacement; and (ii) a relatively shallow‐emplaced (as supported by textures and temperature of formation), vein‐controlled mineralization occurring mainly as veins and veinlets of various shapes (sheeted, single, stockworks, and crustiform), breccias, and disseminations. Whereas Au, Bi, and Cu mineralization from skarn is associated with hydrous retrograde alteration phases (actinolite, ferro‐actinolite, hastingsite, cannilloite, and hornblende), numerous alteration types are associated with the vein‐controlled style of mineralization and these include: biotite, phyllic, argillic, propylitic, carbonate, and quartz (silicification) alterations. The mineralization–alteration processes took place over a wide temperature range that is bracketed between 340 and 568°C, as indicated by chlorite and arsenopyrite geothermometers. The Au‐rich Nucleus deposit is characterized by anomalously high content of As and Bi (as much as 1 %), and whereas Au moderately correlates with Bi ( r = 0.40) in the skarn mineralization style (where native Au is spatially associated with native Bi and Bi‐bearing sulfides), the two elements correlate poorly ( r = 0.14) in the vein‐controlled type, in which native Bi‐ and Bi‐sulfide‐bearing veins are locally observed. Sphalerite from the vein‐controlled mineralized type is Fe‐rich (9.92–10.54 mol % FeS) indicative of low sulfidation conditions, as well as high temperature, with the latter further supported by arsenopyrite geothermometry (up to 491°C), low Ag content (3–7 wt.%) in Au, and the high gold fineness (926–964). Whereas molybdenite Re–Os ages from quartz‐molybdenite veins range from 75.8 to 76.2 ± 0.3 Ma, titanite from the skarn type mineralization recorded CA ID‐TIMS and LA ICP‐MS U–Pb ages of 182.6 ± 2.4 Ma and 191.0 ± 1.5 Ma, respectively, thus precluding any genetic link between the two spatially associated styles of mineralization from the Nucleus deposit area. The Au–Ag–Bi–Cu Nucleus deposit is therefore regarded as a superposed system in which two mineralization types, without any petrogenetic relationship, overlapped, possibly with remobilization of early‐formed mineralization. Abstract : The Nucleus Au‐Ag‐Bi‐Cu Deposit in Yukon is located in the Canadian Portion of the Tintina Au Belt that hosts significant Intrusion‐Related Gold Deposits. The Nucleus Deposit contains two contrasting and overlapping styles of mineralization including skarn and vein‐controlled deposits. Whereas the vein controlled mineralization is of 75.9 ± 0.3 Ma (molybdenite Re‐Os age), skarn yielded titanite CA ID‐TIMS and titanite LA ICP‐MS ages of 182.6 ± 2.4 Ma and 191.0 ± 1.5 Ma, respectively.